Pengaruh Current Ratio, Debt To Equity Ratio, Return On Assets Terhadap Dividend Payout Ratio (Studi Kasus Perusahaan Manufaktur Periode 2012-2016) - Yudea Yudea (Jurnal Ekonomi Dan Bisnis, 2017)
This study intends to examine the influence of current ratio, debt to equity ratio, and return on assets to dividend payout ratio in manufacturing companies. This analysis uses independent variables is current ratio, debt to equity ratio and return on assets. Dependent variable is dividend payout ratio. Investment can be interpreted as a commitment to invest some funds at this time with the aim of obtaining profits in the future. Investors have the main goal in investing funds into the company to seek income or return on investment in the form of dividends. Therefore, the authors want to examine about any variable that can affect the rate of return of dividends. The sample of this study is the financial statements of manufacturing companies listed on the Indonesia Stock Exchange (IDX) period 2012-2016. The research method used in this study is a quantitative research method with the sample used data in the form of numbers and statistical value obtained from the annual financial statements of the company. The result of this research shows that the current ratio, debt to equity ratio has significant influence on the dividend payout ratio. While return on assets does not have a significant effect on dividend payout ratio which means that this variable does not give effect to dividend distribution to shareholders.